A modified mode I cohesive zone model for the delamination growth in DCB laminates with the effect of fiber bridging. (15th June 2020) - Gong, Yu; Hou, Yixin; Zhao, Libin; Li, Wangchang; Zhang, Jianyu; Hu, Ning
Highlights: A three-linear CZM is proposed based on the microscopic failure mechanism of the delamination in composite laminates. Bridging stress is experimentally obtained by J-integral method and implemented into the new CZM using a user-subroutine UMAT. A sensitivity analysis shows that the interfacial strength has little effect on the simulated results. Abstract: Fiber bridging has a significant influence on the delamination propagation behavior in multidirectional composite laminates. Traditional pure mode I bilinear cohesive zone models (CZM) do not consider the effect of fiber bridging and result in an inaccurate simulation on the delamination behavior. This study proposed a physical-based three-linear CZM superposed by two bilinear CZMs, which represent two different phenomena including the quasi-brittle matrix fracture characterized by a higher peak stress and a shorter critical opening displacement, and the fiber bridging characterized by a lower peak stress and a longer critical opening displacement, respectively. The three-linear CZM was implemented in the commercial FE software using a user-subroutine UMAT. Double Cantilever Beam (DCB) tests on the multidirectional composite laminates with 0°/5° and 45°/−45° interfaces conducted in our previous studies are shown to have large-scale fiber bridging in mode I delamination and are used to provide experimental data for calibrating the new CZM. Good agreements between the predicted and tested results can be achieved by adopting this new CZM, demonstrating its applicability on predicting the mode I delamination behavior in composite laminates with the effect of fiber bridging. Graphical abstract: Image, graphical abstract